Bell’s Palsy : Tinjauan Pustaka - Fidela Anindya Atha; Ratna Dewi Puspitasari; Ramadhana Komala (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Bell’s Palsy is an acute peripheral facial nerve paralysis that causes unilateral facial weakness. The exact cause remains unclear but is suspected to involve anatomical factors, infections, viral reactivation (especially Herpes Simplex Virus), ischemia, inflammation, and cold exposure. The incidence is 20-30 per 100,000 people annually, with no gender or age preference, though it is more common in middle-aged and elderly individuals. Risk factors include diabetes, pregnancy, preeclampsia, obesity, and hypertension. Symptoms develop suddenly, peaking within 48 hours, and include facial asymmetry, difficulty closing the eyes, eating, speaking, and sensory-motor disturbances. Most cases recover spontaneously within weeks to months, but corticosteroids and antiviral therapy can accelerate recovery. Proper diagnosis is crucial as Bell’s Palsy is often mistaken for stroke or other neurological disorders.